Translation Policies in Legal and Institutional Settings - Bourguignon, Marie; Nouws, Bieke; van Gerwen, Heleen (Translation, Interpreting and Transfer, 2021)
This edited volume documents the state of the art in research on translation policies in legal and institutional settings. Offering case studies of past and present translation policies from several parts of the world, it allows for a compelling comparison of attitudes towards translation in varying contexts. The book highlights the virtues of integrating different types of expertise in the study of translation policy: theoretical and applied; historical and modern; legal, institutional and political. It effectively illustrates how a multidisciplinary perspective furthers our understanding of translation policies and unveils their intrinsic link with topics such as multilingualism, linguistic justice, minority rights, and citizenship. In this way, each contribution sheds new light on the role of translation in the everyday interaction between governments and multilingual populations.